Caracterização de tinta de caneta esferográfica azul por espectroscopia Raman para aplicação na área forense - Rodrigues, Sergio Licinio (2021)
One of the tools for the forensic analysis of inks is Raman spectroscopy. One of the main advantages of the technique for Documentoscopy is it non-destructive character, without need for sample preparation and applications in situ. Raman scattering is the result of the inelastic collision between light and matter, excited it, through a virtual state, to a final state different from the initial one. Ballpoint pens are widely used writing instruments due to their high availability and low cost. The ink in these pens can be divided into colorants and vehicles. Among the colorants, Copper Phthalocyanine (CuPc) is highlighted as one of the main representatives. Several studies have analyzed the Raman spectrum of CuPc in crystalline form or thin films. The analysis of the Raman spectrum of blue ballpoint ink when applied by the pen on the paper highlighted 5 more intense bands. With a maximum error of 6 cm −1 , these bands can be associated with CuPc. Even after a period of drying the trace on the paper, measurements taken in perpendicular orientations did not show anisotropic behavior evident in the region between 80 to 1800 cm −1.